Penerapan Metode Mamdani dalam Menentukan Tingkat Resiko Gizi Buruk Ibu Hamil di Puskesmas Pemancungan - Dini Kamala Sari; muhammad subhan (Journal of Mathematics UNP, 2018)
Abstract –Assessment of nutritional status is very important during pregnancy, because it greatly affects the health of the mother and fetus. To reduce mistake in nutritional assessment and the lack of certainty to find out how much the level of risk of malnutrition in pregnant women, fuzzy logic can be used. This study uses the Mamdani  method with the affirmation of the centroid method. There are three variables used in this study which is mid upper arm, hemoglobin and weight gain. The result of this study of eighteen pregnant women obtain ten at high risk, three at moderate risk, and five people at low risk.